Differential regulation of apical–basolateral dendrite outgrowth by activity in hippocampal neurons - Yuan, Yang; Seong, Eunju; Yuan, Li; Singh, Dipika; Arikkath, Jyothi (Frontiers in Cellular Neuroscience, 2015)
Hippocampal pyramidal neurons have characteristic dendrite asymmetry, characterized by structurally and functionally distinct apical and basolateral dendrites. The ability of the neuron to generate and maintain dendrite asymmetry is vital, since synaptic inputs received are critically dependent on dendrite architecture. Little is known about the role of neuronal activity in guiding maintenance of dendrite asymmetry. Our data indicate that dendrite asymmetry is established and maintained early during development. Further, our results indicate that cell intrinsic and global alterations of neuronal activity have differential effects on net extension of apical and basolateral dendrites. Thus, apical and basolateral dendrite extension may be independently regulated by cell intrinsic and network neuronal activity during development, suggesting that individual dendrites may have autonomous control over net extension. We propose that regulated individual dendrite extension in response to cell intrinsic and neuronal network activity may allow temporal control of synapse specificity in the developing hippocampus.